DAMPAK PENGGUNAAN GAME ONLINE TERHADAP SISWA DI MTsS ULEE TUTUE ACEH UTARA - Amiruddin Amiruddin (Kalam: Jurnal Agama dan Sosial Humaniora, 2019)
Online game is one type of game that involves many players who use LAN (local area network) or the Internet. Its presence is agreed to have neglected students by spending to play online games which in turn makes student achievement decreases. This issue is the focus of research, mostly related to the use of online games and their solution to the students of MTsS Ulee Tutue. Qualitative research uses observation, interview and documentation techniques for data collection. This research resulted in positive and negative findings. The positive impact can be made as entertainment, as a venue for concentration training and making friends. Besides positive thinking is that students can control themselves, train sports, train intelligence, creativity, logic and nerve reflexes of the brain and hands when playing games. Meanwhile, the negative is to waste time, waste and take payment as a student. The solution is to solve things that are new in the world of the internet, teach time discipline, and improve social relationships with friends and stay away from online games gradually.